Numerical modeling of material removal mechanism and surface topography for gear profile grinding. (April 2022) - Xiao, Yuliang; Wang, Shilong; Ma, Chi; Wang, Sibao; Yang, Wenhan; Xia, Changjiu; Wang, Jun
Abstract: Gear profile grinding is more complex than surface grinding owing to the specific shape of the grinding wheel and geometric characteristics of the gear tooth, resulting in difficulties in modeling grinding components. Consequently, conventional grinding models tend to fail. To address this issue, a novel semi-analytical modeling method of the material removal mechanism and surface generation for gear profile grinding is proposed. Firstly, the grinding wheel model is represented by a multi-information fusion matrix that contains kinds of information about grinding grits. Compared with the traditional models that require several matrices to represent respective information, the proposed wheel model incorporates multi-dimensional information without extending the original matrix size and data length, which is more efficient. Then, a numerical model for the grinding process is developed by analyzing grit kinematics and grit-workpiece contact to reveal the material removal mechanism, and it is found that the cross-section shape of 3D cutting chips changes in the direction of the contact line. Furthermore, a surface topography model is established considering the specific pile-up effect. In this process, based on the length conservation of the tooth profile curve after straightening, the body Boolean operation is replaced by matrix calculation which reduces the dimension of data from 3D to 2D. Thus, computing time is reduced greatly, and this method does not require knowledge of the generation mechanism for tooth profile. Finally, experiments are conducted and the effects of grinding parameters on surface topography are investigated. The experimental results match well with model predictions, proving the model is effective. This work provides further understanding of the material removal mechanism for gear profile grinding. Meanwhile, it can also be extended and applied to other grinding processes for workpieces with complex geometry.